A theoretical framework for designing a multimedia app in increasing knowledge and perceived awareness towards cyber-bullying among adolescents / Nadia Abdul Wahab and Wan Ahmad Jaafar Wan Yahaya - Abdul Wahab, Nadia; Wan Yahaya, Wan Ahmad Jaafar (UiTM Cawangan Perlis, 2017)
This paper discusses the theoretical framework in designing and developing a multimedia app intended to increase knowledge and perceived awareness towards cyber-bullying among adolescents. Given that cyber-bullying has become more serious lately, steps should be taken to ensure that this threat is curtailed (Willard, 2007). Other than the conventional methods and the involvement of parents, schools and the society in curtailing this problem, other initiatives that could be taken include developing a Multimedia App on tablets that would be able to assist adolescents in increasing their knowledge and awareness on cyber-bullying. Development of an interactive Multimedia App that comes with attractive graphics, audio and animation have great potential in attracting the interest of adolescents in gaining a deeper understanding of this issue. Therefore, the theoretical framework maps and integrates all relevant theories, principles and guidelines to form a concrete pathway for the design and development of the multimedia app.